2021
DOI: 10.1136/bmjresp-2021-001002
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of mortality among patients hospitalised with COVID-19 in a critical care or hospital care unit: analysis of the French national medicoadministrative database

Abstract: ObjectiveTo explore mortality risk factors for patients hospitalised with COVID-19 in a critical care unit (CCU) or a hospital care unit (HCU).DesignRetrospective cohort analysis using the French national (Programme de médicalisation des systèmes d’information) database.SettingAny public or private hospital in France.Participants98 366 patients admitted with COVID-19 for more than 1 day during the first semester of 2020 were included. The underlying conditions were retrieved for all contiguous stays.Main outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…In the present study, we observed a high in-hospital mortality rate of 41.3% among patients with precapillary PH, including a 23% in-hospital mortality among those with group 1 PAH. The in-hospital mortality of 41% for patients with PH is more than double the overall estimated in-hospital mortality of 18.8% due to COVID-19 in France ( 22 , 23 ). In addition to the deleterious effects of COVID-19 on the pulmonary vasculature ( 24 ), there is a strong relationship between right ventricular (RV) dysfunction and death in all comers who are hospitalized with COVID-19 ( 25 ).…”
Section: Discussionmentioning
confidence: 91%
“…In the present study, we observed a high in-hospital mortality rate of 41.3% among patients with precapillary PH, including a 23% in-hospital mortality among those with group 1 PAH. The in-hospital mortality of 41% for patients with PH is more than double the overall estimated in-hospital mortality of 18.8% due to COVID-19 in France ( 22 , 23 ). In addition to the deleterious effects of COVID-19 on the pulmonary vasculature ( 24 ), there is a strong relationship between right ventricular (RV) dysfunction and death in all comers who are hospitalized with COVID-19 ( 25 ).…”
Section: Discussionmentioning
confidence: 91%
“…Based on three of these studies, risk estimates were higher (non-overlapping 95% CIs) for hematological cancers (aHR = 2.80 [2.08-3.77], 1 study 19 ; aOR = 2.13 [1.68-2.68], 2 studies). 20,21 Risk estimate results were similar based on studies of hospital inpatients with COVID-19, with a slightly lower aHR estimate for any/solid cancers (any/solid cancer: aHR = 1.34 [1.19-1.50], 5 studies [23][24][25][26][27] ; aOR = 1.66 [1.34-2.06], 8 studies [28][29][30][31][32][33][34][35] ; hematological cancer: aOR = 2.20 [1.97-2.46], 1 study 30 ). For studies of hospital inpatients with COVID-19, there was moderate to high overall risk of bias in the hazard ratio meta-analysis (moderate risk for one study contributing 52% weight, and high risk of bias for other studies due to exposure measurement or potential over-adjustment), and moderate to high risk of bias in the odds ratio meta-analyses (four studies and 50% weight with moderate and high overall risk of bias each, due to exposure measurement, adjustment for confounders or potential overadjustment).…”
Section: Resultsmentioning
confidence: 58%
“…The 39 studies included data from 12 countries (Table 1). 16‐54 After exclusion of studies due to overlapping data, 33 studies were included in the quantitative analyses, of which 28 were included in the main analyses (including analyses restricted to cancer types or metastatic/non‐metastatic cancers), with data from >27 565 252 individuals including >229 642 people with active or recent cancer. Of these 28 studies, 4 focused on the general population, 9 on all people with COVID‐19 and 16 on hospital inpatients with COVID‐19 (one study provided results for both the general population and all people with COVID‐19).…”
Section: Resultsmentioning
confidence: 99%
“…Rationale . Age is one of the main prognostic factors of a poor clinical outcome (hospitalization, need for intensive care or death) in patients infected with SARS-CoV-2, with a strong association with the age of 65 years and a maximum from the age of 70 years onwards, both in unvaccinated and vaccinated populations [ 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 ]. There is also a correlation between comorbidity and poorer clinical outcome, including mortality, at all ages, although particularly after 60 years of age.…”
Section: Resultsmentioning
confidence: 99%